Sosialisasi dan Pengenalan Teknologi Komputer kepada Masyarakat - Garlyanto Basri; Kenny Devin Wijaya; Camelia Yeominda; Sandy Kurniawan; Nick Kurniawan; Kiky Kurniawan; Ellis Ellis; Surya Dharma Samosir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
In this day and age, technology is increasingly developing as computer technology can ease our daily work, this causes computers to be needed in more fields without exception because of their very efficient and effective functions, and also research in the Javanese village, the author supports it computer facilities are still not there, there are children, there is nothing on the computer, including history, this can give a bad view of the compilation of children who are adults and ready to go into the workforce but do not find what a computer is, the intended team will create a computer science theory system for children of Javanese villagers in the hope that children in Javanese villages can get to know computers better, how to operate and the history of the computer itself.